(untitled) (International Journal of Contemporary Security Studies, 2024)
Main goal of the paper is to analyze some of the most important implications of the contemporary international relations to the security of Arctic region. As a reflexion of the current state of the international relations and the revitalization of the „Cold war“ interactions among key global players, Arctic region has been subject of relatively intensive (re)militarization from both – Russian and „Western“ – sides, as well as of military reconfiguration, in a sense that NATO, through the admission of Finland and Sweden in its membership in April 2023 and March 2024, significantly strenghtened its Baltic, Nordic and Arctic flanks, as well as its presence at the Russian border. The analysis of the subject has been done within the theoretical framework of the science of international relations and by using the selected scientific methods, such as content analysis, inductive and deductive methods, as well as the comparative analysis. One of the conclusions of the analysis is that, as an implicitaion of its (re)militarization, military reconfiguration and of the state of contemporary international relations in general, military security of the Arctic region is by far predominant dimension of its security at the moment. Additional complicating moment regarding the complex situation in the Arctic comes with the „Chinese factor“ and the strong intention of Beijing, primarily over Moscow, to gradually impose itself as a inevitable political, economic, as well as security „force“ in the Arctic region. Western countries, led by the US, the intention of China see as a direct threat to their national interests, while the Russian Federation`s long term best interests, no matter how important its partnership with Beijing is right now, is to keep its presence and influence in the region within the acceptable framework.